Triple resonance ¹⁵Ν NMR relaxation experiments for studies of intrinsically disordered proteins - Srb, Pavel; Nováček, Jiří; Kadeřávek, Pavel; Rabatinová, Alžbeta; Krásný, Libor; Žídková, Jitka; Bobálová, Janette; Sklenář, Vladimír; Žídek, Lukáš (Journal of biomolecular NMR, 2017)
Description of protein dynamics is known to be essential in understanding their function. Studies based on a well established [Formula: see text] NMR relaxation methodology have been applied to a large number of systems. However, the low dispersion of [Formula: see text] chemical shifts very often observed within intrinsically disordered proteins complicates utilization of standard 2D HN correlated spectra because a limited number of amino acids can be characterized. Here we present a suite of triple resonance HNCO-type NMR experiments for measurements of five [Formula: see text] relaxation parameters ([Formula: see text], [Formula: see text], NOE, cross-correlated relaxation rates [Formula: see text] and [Formula: see text]) in doubly [Formula: see text],[Formula: see text]-labeled proteins. We show that the third spectral dimension combined with non-uniform sampling provides relaxation rates for almost all residues of a protein with extremely poor chemical shift dispersion, the C terminal domain of [Formula: see text]-subunit of RNA polymerase from Bacillus subtilis. Comparison with data obtained using a sample labeled by [Formula: see text] only showed that the presence of [Formula: see text] has a negligible effect on [Formula: see text], [Formula: see text], and on the cross-relaxation rate (calculated from NOE and [Formula: see text]), and that these relaxation rates can be used to calculate accurate spectral density values. Partially [Formula: see text]-labeled sample was used to test if the observed increase of [Formula: see text] [Formula: see text] in the presence of [Formula: see text] corresponds to the [Formula: see text] dipole-dipole interactions in the [Formula: see text],[Formula: see text]-labeled sample.
Keywords: DNA řízené RNA-polymerasy; Hydrogen; Intrinsically Disordered Proteins; vnitřně neuspořádané proteiny; izotopy dusíku; nukleární magnetická rezonance biomolekulární; izotopy uhlíku; Intrinsically disordered proteins; Nuclear magnetic resonance; Relaxation; Carbon Isotopes; Non-uniform sampling; Nitrogen Isotopes; Nuclear Magnetic Resonance, Biomolecular; vodík; Bacillus subtilis; DNA-Directed RNA Polymerases